A Loan Word in the Noble Qur'an - Andri Purwanto (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
The objective of this research is to analyze the Islamic terms according translation theories. One of the translation theories is modifying a loan word with meaning components, i.e. form, additions, couplets, synonim, comparison, and the last is a classifier. This theory is introduced by Larson in dealing with cultural and biblical terms.This research is a library research and the source data is taken from the Noble Qur’an, English translation and commentary translated by Dr Muhammad Taqi-ud-Din Al-Hilali dan Dr Muhammad Muhsin Khan. The research discusses some translation theories, i.e. (1) a loan with features of form, (2) a loan word with function, (3) a loan word with form and function, (4) a loan word with a comparison, (5) a loan word with a classifier, (6) a loan word with couplets, triplets, quadruplets and quintaplets, (7) a loan word with a synonim, and (8) a loan word with a a synonim plus reference, (9) a loan word with no modification.